Mama sierra (2020)
The Sierra Nevada de Santa Marta is the most irreplaceable ecosystem in the world. Mama Sierra is a deck of cards that, through the visualization of data of this sacred mountain, aims to expose the importance of protecting and conserving the heart of the world. In the same way, it also seeks to generate dialogues between the actors about the roles that must be fulfilled around it.